2020
DOI: 10.1074/jbc.ra120.013455
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus NS3-4A protease regulates the lipid environment for RNA replication by cleaving host enzyme 24-dehydrocholesterol reductase

Abstract: Many RNA viruses create specialized membranes for genome replication by manipulating host lipid metabolism and trafficking, but in most cases, we do not know the molecular mechanisms responsible or how specific lipids may impact the associated membrane and viral process.  For example, hepatitis C virus (HCV) causes a specific, large-fold increase in the steady-state abundance of intracellular desmosterol, an immediate precursor of cholesterol, resulting in increased fluidity of the membrane where HCV R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Conditions that alter homeostasis ,, and introduce oxidatively reactive sterols into the cellular lipidome have the potential to perturb critical steps in the infection process. Indeed, there is evidence that cellular 7-DHC gives highly reactive electrophilic oxysterols upon peroxidation, see Figure A. These species adduct to several lipid synthesis and transport proteins, prominent among these proteins being constituents of COPI, the transport complex involved in traffic between the Golgi and endoplasmic reticulum and ACSL4, an acyl-CoA synthetase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditions that alter homeostasis ,, and introduce oxidatively reactive sterols into the cellular lipidome have the potential to perturb critical steps in the infection process. Indeed, there is evidence that cellular 7-DHC gives highly reactive electrophilic oxysterols upon peroxidation, see Figure A. These species adduct to several lipid synthesis and transport proteins, prominent among these proteins being constituents of COPI, the transport complex involved in traffic between the Golgi and endoplasmic reticulum and ACSL4, an acyl-CoA synthetase.…”
Section: Discussionmentioning
confidence: 99%
“…64−69 Likewise, many viruses use cholesterol-rich plasma membrane lipid raft microdomains to bud from the infected host cells, 69−71 and cholesterol is important for intracellular trafficking processes for the assembly of replication complexes and for viral genome replication. 72,73 Conditions that alter homeostasis 3,74,75 and introduce oxidatively reactive sterols into the cellular lipidome have the potential to perturb critical steps in the infection process. Indeed, there is evidence that cellular 7-DHC gives highly reactive electrophilic oxysterols upon peroxidation, see Figure 6A.…”
Section: Dose−response Effects Of Drugs On Cholesterolmentioning
confidence: 99%
“…Modulation of the activity of DHCR24 has been observed during infection of mammalian viruses (Tallorin et al. , 2020), confirming the important role of cholesterol metabolism in viral infections.…”
Section: Discussionmentioning
confidence: 69%
“…PI4P could attract lipid transport proteins (oxysterol-binding protein (OSBP), four-phosphate adaptor protein 2 (FAPP2), NPC1, and ceramide transfer protein (CERT) to deliver glycosphingolipids, cholesterol, and ceramide to RO, respectively [ 16 , 59 , 60 ]. Recently, it was reported that HCV NS3/4A protease controls the activity of 24-dehydrocholesterol reductase (DHCR24), catalyzing the conversion of desmosterol to cholesterol and regulating the lipid environment for HCV RNA replication [ 61 ]. In contrast, cholesterol-25-hydroxylase induced by interferon could block MW formation via the production of 25-hydroxycholesterol and thus restrict HCV replication [ 62 ].…”
Section: Viral Replication Organelles (Ro)mentioning
confidence: 99%